2015
DOI: 10.1017/s071498081500046x
|View full text |Cite
|
Sign up to set email alerts
|

Driving Skills Training for Older Adults: An Assessment of DriveSharp

Abstract: RÉSUMÉ Les procédures de formation cognitive informatique visent à augmenter la sécurité en améliorant les compétences relatives à la conduite, comme la vitesse-de-traitement et le Useful Field of View. L'étude actuelle a évalué l'efficacité du DriveSharp dans la formation des conducteurs âgés dans un cadre de classe réaliste. Les participants (n = 24) ont assisté à 10 heures de cours de DriveSharp pendant 5 semaines. Les séances pré- et post-test ont evalués améliorations sur un essai dynamique de la percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 34 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…However, those results should be analysed with caution since the dependent variable is based on self-report through the mobility questionnaire. Contrary to the positive findings mentioned above, another reviewed study showed that 5 weeks of training with 2 weekly 60-min sessions guided by a facilitator did not reveal any significant benefit associated with the intervention [46]. This could be due in part to the type of variable used, i.e.…”
Section: Computer-based Trainingmentioning
confidence: 69%
“…However, those results should be analysed with caution since the dependent variable is based on self-report through the mobility questionnaire. Contrary to the positive findings mentioned above, another reviewed study showed that 5 weeks of training with 2 weekly 60-min sessions guided by a facilitator did not reveal any significant benefit associated with the intervention [46]. This could be due in part to the type of variable used, i.e.…”
Section: Computer-based Trainingmentioning
confidence: 69%